2023
DOI: 10.3389/fcell.2023.1148792
|View full text |Cite
|
Sign up to set email alerts
|

CDK4/6 inhibitor resistance in estrogen receptor positive breast cancer, a 2023 perspective

Abstract: CDK4/6 inhibitors have become game-changers in the treatment of estrogen receptor-positive (ER+) breast cancer, and in combination with endocrine therapy are the standard of care first-line treatment for ER+/HER2-negative advanced breast cancer. Although CDK4/6 inhibitors prolong survival for these patients, resistance is inevitable and there is currently no clear standard next-line treatment. There is an urgent unmet need to dissect the mechanisms which drive intrinsic and acquired resistance to CDK4/6 inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 129 publications
0
4
0
Order By: Relevance
“…39 Increasing evidence suggests that CDK4/6I resistance can result from RB1 inactivation; CDK6, CCNE1/2, and aurora kinase A overexpression; and mutational activation of FGFR, ERBB2, AKT1, and RAS oncogenes. 40,41 The PALOMA-3 trial (ClinicalTrials.gov identifier NCT01942135) revealed that acquired ERBB2 mutations contribute to CDK4/6i resistance. 42 These mutations can enhance HER2 pathway signaling and sensitize tumors to HER2 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…39 Increasing evidence suggests that CDK4/6I resistance can result from RB1 inactivation; CDK6, CCNE1/2, and aurora kinase A overexpression; and mutational activation of FGFR, ERBB2, AKT1, and RAS oncogenes. 40,41 The PALOMA-3 trial (ClinicalTrials.gov identifier NCT01942135) revealed that acquired ERBB2 mutations contribute to CDK4/6i resistance. 42 These mutations can enhance HER2 pathway signaling and sensitize tumors to HER2 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that the hepatocyte growth factor/mesenchymal-epithelial transition factor (c-MET) signaling pathway serves a key role in carcinogenesis, regulation of tumor microenvironment, metastasis and drug resistance (58,59). Aberrations in c-MET have been described among several potential mechanisms of resistance to CDK4/6is (60). Increased c-MET expression, frequently observed in HR + /HER2breast cancer (61,62), is associated with disease stage, progesterone receptor levels, Ki67 index and worse survival (63).…”
Section: Discussionmentioning
confidence: 99%
“…In melanoma, multiple mutations can affect CDK4/6 activity and increase proliferation by promoting the G1-S transition [53]. Interestingly, CDK4/6 can be activated beyond the MAPK pathway via the estrogen receptor (ER) signaling pathway, which is common in breast cancer [54,55]. Because CDK4/6 inhibitors have already been developed and effectively used to treat breast cancer tumors, clinicians are testing the efficacy of CDK4/6 inhibitors in combination with other inhibitors to combat melanoma.…”
Section: Non-braf and Mek-related Biomarkersmentioning
confidence: 99%